Aortitis presenting as acute myeloid leukemia - A case report. (August 2022) - Ireifej, Branden; Freijat, Majd; Song, David; Shah, Nagma; Mukherjee, Dattatreya; Jaiswal, Vikash
Abstract: Introduction: Aortitis can be an initial presentation of many diseases, but most often include large cell vasculitis. Case presentation: We present a case of a 53 year old female who presented with a myriad of symptoms including abdominal pain, nausea, fever, and headaches. CT scan of the chest showed an inflamed aorta with an initial concern for a large cell vasculitis, but found later to be from her underlying acute myeloid leukemia (AML). Discussion/conclusion: Our case emphasizes the importance of aortitis being the initial presentation of a multitude of diseases including malignancy. It remains important, especially for rheumatologists, to consider blood cancers when presented with aortitis. Background/introduction: Aortitis can be an initial presentation of many diseases, but most often include large cell vasculitis. We describe a case of aoritis being the initial presentation of AML. Methods: SCARE 2020 Guidelines.